Employee benefits in multinational firms: Empirical evidence for Romania and Serbia - Caran Margareta; Georgiana-Noja Gratiela (Megatrend Revija, 2015)
The paper aims to analyze post-employment benefits provided by multinational firms, focusing on retirement advantages and pension systems in Romania and Serbia from a comparative empirical perspective. Economic literature highlights the essential role played by pension schemes in assuring a proper level of income after retirement, thus reducing poverty and increasing productivity, with significant positive implications upon overall economic activity. our research is based on developing several double-log fixed and random effects models, as well as a dynamic and distributed lags model, using a panel structure over the 2005- 2013 period and a complex set of indicators (national accounts - GDP total and per capita; labor market - employment, unemployment, productivity, earnings; secondary and tertiary education; pension specific data - general beneficiaries, old age and survivor pensioners, total and by gender, and pension expenses as percentage of GDP). The results show that pensions represent an incentive for employees leading to an increase in resource productivity. At the same time, old age pensions are positively shaping economic growth and employment for the two countries considered, significantly reducing the poverty rate for pensioners. Nevertheless, the two pensions systems are modelled by the economic activity, educational background of employees, as well as by the level of net earnings.